Exploration of Male Views and Patriarchal in Han Kang's The Vegetarian: Masculinity and the Gaze - Panta, Sudil; Adhikari, Tara Prasad (NPRC Journal of Multidisciplinary Research, 2025)
Background: This study aims to examine the representation of masculinity and intends to look into Han Kang’s The Vegetarian, attempting to explore how male views represent patriarchal anxieties in the Korean cultural context, with an emphasis on the male character Mr. Cheong (Yeong-Hye's husband), the brother-in-law, and the father.Methods: This research adopts a qualitative approach as a methodology, supported and discussed under textual analysis. It is mainly performed by close reading of The Vegetarian; particularly emphasizing passages that show how male behaviour portrays the male gaze and the deployment of traditional patriarchal domination.Results: By analysing gender, power dynamics, and social norms, an intersectional perspective is rendered, which offered an opinion on how to explain patriarchal forces and functions through the male gaze and how they respond to Yeong-Hye's deviance. The main focus revolves around male characters' inspection, evaluation, and control of Yeong-Hye's conventional gender role through textual analysis. The examination of key scenes in which Yeong-Hye's body and choices are influenced and men's power, desires, and frustrations have also been identified.Conclusion: In The Vegetarian, Han Kang ably explored the fragile patriarchal notion of masculinity within the grid of masculine anxiety and the suffocating ways of the male gaze. While it zeroes in on Yeong-Hye’s father, brother-in-law, and husband, the novel exemplifies how the structures of patriarchy use violence, objectification, and domination as strong modes of suppressing women's agency. When conventional masculinity is faced with female agency, Mr. Cheong's inability to negotiate Yeong-Hye’s vegetarianism with his strict desires for a submissive wife highlights how insecure it is.